MINIMIZING STUDENTS’ ANXIETY TO SPEAK ENGLISH BY USING SOCIO-AFFECTIVE STRATEGIES - Heldi Maulana (Journal of English Education Program (JEEP), 2016)
This study was conducted to investigate the factors that cause students’ anxiety to speak English, the teacher use socio-affective strategies to minimize student’ anxiety to speak English. To practice speaking is therefore a central part of English lessons in schools. However, to make students speak the target language is not always easy and there can be several different reasons. This study employed descriptive qualitative case study. The population the writer took the students at the eleventh grade of SMAN 1 Pangandaran that consist of 320 students and chose the sample of 1 class consist of 40 students and an English teacher as the sample of this study. The data were obtained from observation, questionnaire and interview. Based on the instruments used by the writer in order to collect the data for answering the research questions about the causes of students’ anxiety and the teacher’s effort to minimize students’ anxiety to speak English by using socio-affective strategies, the writer summarized each point from each research questions above. The findings showed that the factors caused students' anxiety to speak English were: fear of speaking class, students’ low proficiency in speaking English, fear of making mistake, shy to speak English, and self-related cognition. Moreover, socio-affective strategies which were used by the teacher to minimize their anxiety were: motivated them and gave them some positive reinforcements as the way to minimize the students’ anxiety to speak English. Furthermore, those strategies could reduce the students’ anxiety to speak English.Keywords: speaking English, students’ anxiety, socio-affective strategies.